Assessing Student Learning Experiences in Integrated Design Projects of a Malaysian Civil Engineering Programme - Ling, Jen Hua (Papanda Publishier, 2025)
This study investigated the student learning experiences in the Integrated Design Project (IDP) of a Malaysian civil engineering programme. Understanding these experiences is crucial for improving the course and better preparing students for professional practice. The study evaluated the current implementation against the Engineering Accreditation Council (EAC) requirements for validity and conducted a questionnaire survey to assess students' learning experiences for effectiveness. The survey evaluated four aspects of the learning experience, including commitment and participation, teaching and learning resources, learning mechanisms and processes, and overall satisfaction. The results indicated that the IDP met all 11 accreditation requirements set by the EAC, and students generally had positive learning experiences, with 93.8% of respondents enjoying the IDP class. These results suggest that the IDP effectively prepares students for real-world challenges, especially for those working within the local industry. However, the study also noted some limitations of the IDP. Each student played key roles in only 5.4 out of 13 topics (41.5%), and 43.8% of the students lacked collaborative learning experiences. To address these issues, supervisors could encourage peer teaching and peer review to broaden students' understanding beyond their limited topics.